TEACHING PRESCHOOL CHILDREN TO THINK LOGICALLY - Ibragimova Lizakhan Avezovna (Journals Park Publishing, 2023)
Preschool education is a critical period in a child's cognitive development, providing the foundation for future academic success. While it might seem early to introduce complex concepts like logical thinking to preschoolers, research indicates that fostering logical reasoning skills at an early age can have profound and lasting effects on a child's cognitive abilities. In this article, we will explore the importance of teaching preschool children to think logically and provide practical strategies for educators and parents to implement in nurturing logical reasoning in their young learners.
Keywords: Preschool education, Logical thinking, Cognitive development, Early childhood education, Problem-solving skills, Critical thinking, Curriculum integration, Technology in education, Parental involvement, Lifelong learning.